MORTAL PULPOTOMY ON CHILDREN WITH VENTRICULAR SEPTAL DEFECT - Devi N. R. Devy; Suwelo I. S. Suwelo (Faculty of Dentistry, Universitas Indonesia, 2006)
Congenital heart disease is a condition of heart anomaly found since birth. The most common is ventricular septal defect whereby an aperture is found in the partition of heart chamber. It is estimated that 40,000 newborn in Indonesia have this defective condition. Dental treatment for patients with such condition must be undertaken in a very cautious way. Tooth with multiple caries can potentially lead to endocarditis bacteria. As such, dentist must be watchful on dental treatment that may worsen the patient's condition. To prevent endocarditis bacteria, a prophylaxis antibiotic is required as recommended by the American Heart Association (AHA). In this particular case, a dental treatment was undertaken to a child patient with congenital heart disease. Previously, the patient has undergone dental treatment in the form of multiple extractions under general anesthesia before conducting cardiac surgery. In this case the treatment includes mortal pulpotomy, GIC restoration, and fissure sealant - all conducted in one visit under general anesthesia. A year after the treatment, there are no complaints from the patient and no irregularity on x-ray results.